Looking beyond human papillomavirus (HPV) genotype 16 and 18: Defining HPV genotype distribution in cervical cancers in Australia prior to vaccination. Issue 8 (14th July 2017) - Brotherton, Julia M.L.; Tabrizi, Sepehr N.; Phillips, Samuel; Pyman, Jan; Cornall, Alyssa M.; Lambie, Neil; Anderson, Lyndal; Cummings, Margaret; Payton, Diane; Scurry, James P.; Newman, Marsali; Sharma, Raghwa; et al.
Abstract : Australia has implemented a high‐coverage HPV vaccination program but has not, to date, established the distribution of HPV types that occur in cervical cancers in Australia. This information is important for determining the potential for cervical cancer prevention with both current and broader spectrum HPV vaccines. We analysed 847 cervical cancers diagnosed 2005 to 2015 in tertiary centres in the three most populous Australian states with resolution of specimens containing multiple HPV types using laser‐capture microdissection. Archived FFPE tissue was reviewed by specialist pathologists, sandwich sectioned, and initially whole‐tissue sections genotyped for HPV. Samples were first genotyped using SPF10‐LiPA25 (version 1). Negative samples were screened with DNA ELISA kit HPV SPF10, followed by genotyping with SPF+ LiPA if ELISA positive. If still negative, samples were tested on a qPCR assay targeting the E6 region of HPV16, 18, 45 and 33. Of the 847 cancers (65.1% squamous, 28.7% adenocarcinoma, 4.3% adenosquamous, 2.0% other), 92.9% had HPV detected. Of the HPV‐positive cancers, 607 of 787 (77.1%) contained HPV16 or 18, 125 of 787 (15.9%) contained HPV31/33/45/52 or 58, and 55 (7.0%) another HPV type. There was a strong correlation between HPV type and age, with younger women most likely to have HPV16/18 detected and least likely HPV negative. Our findings indicate that cervical cancers diagnosed in Australia more frequently contain HPV16/18 than in international series. This could be due to cervical screening in Australia increasing the proportion of adenocarcinomas, in which types 18 and 16 more strongly predominate, due to prevention of squamous cancers. Abstract : What's new? Although Australia was the first country to implement a fully government‐funded vaccination program against human papilloma virus (HPV), it remains unclear what carcinogenic HPV types are most frequent. Here the authors performed a country wide analysis of HPV genotypes in 847 cervical cancers using laser‐capture microdissection. Compared to international studies, HPV16/18 was more (71.8%) and HPV31/33/45/52/58 less frequent (14.8%) with specifically less HPV58 detected, providing important information for the use of current or broader spectrum vaccine types.